1995
DOI: 10.1002/j.1460-2075.1995.tb07191.x
|View full text |Cite
|
Sign up to set email alerts
|

RelA/p65 is a molecular target for the immunosuppressive action of protein kinase A.

Abstract: Stimulation of the protein kinase A (PKA) signalling pathway exerts an inhibitory effect on the proliferation of numerous cells, including T lymphocytes. In CD4+ T helper cells, stimulation of PKA leads to suppression of interleukin 2 (IL‐2) induction, while induction of the genes coding for the lymphokines IL‐4 and IL‐5 is enhanced. We show that the differential effect of PKA activity on induction of the IL‐2 and IL‐4 genes is mediated through their promoters. One major target of the suppressive effect of PKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
115
3
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(136 citation statements)
references
References 91 publications
14
115
3
1
Order By: Relevance
“…PGI 2 analogs were capable of inhibiting NF-B activity in cells expressing the constitutively active form of IKK2, suggesting that a process downstream of IKK2 activity in the NF-B signaling pathway, possibly involving CBP, was affected. Other possible mechanisms for PGI 2 analog/cAMPmediated NF-B inhibition include blocking nuclear translocation of NF-B (10) and decreasing degradation or up-regulation of I B (48). The action of PGI 2 analogs makes them effective inhibitors of proinflammatory cytokines and chemokines and our data indicate that this inhibitory effect of PGI 2 analogs is associated with the decrease of NF-B activity.…”
Section: Discussionmentioning
confidence: 69%
“…PGI 2 analogs were capable of inhibiting NF-B activity in cells expressing the constitutively active form of IKK2, suggesting that a process downstream of IKK2 activity in the NF-B signaling pathway, possibly involving CBP, was affected. Other possible mechanisms for PGI 2 analog/cAMPmediated NF-B inhibition include blocking nuclear translocation of NF-B (10) and decreasing degradation or up-regulation of I B (48). The action of PGI 2 analogs makes them effective inhibitors of proinflammatory cytokines and chemokines and our data indicate that this inhibitory effect of PGI 2 analogs is associated with the decrease of NF-B activity.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies of monocytes/macrophages have shown that cAMP prevents inflammatory stimuli from inducing expression of a distinct set of genes including TNF, tissue factor, E-selectin, and VCAM-1 [32]. One target of cAMP is NF-B, a transcription factor that regulates many inducible genes in activated monocytes and THP-1 cells by a protein-kinase A-dependent mechanism [32,33]. Because LPS and TNF-␣ are both potent activators of NF-B, it is conceivable that P2X 7 R induction requires NF-B activation and that cAMP interferes with this step of induction [34].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that both TNF-a and IL-1/3 activate NF-KB activity in rat astrocytes (Sparacio et al, 1992;Kwon et al, 1996). Elevating cAMP levels in various cell types has been shown to have effects on the transactivating ability of NF-KB, as well as affecting the translocation of NF-KB complexes from the cytoplasm to the nucleus (Ghersa et al, 1994;Satriano and Schlondorff, 1994;Neumann et al, 1995;Ollivier et al, 1996). Hence, inhibition of adhesion molecule gene expression in astrocytes/astroglioma cells by elevating intracellular cAMP levels may be either a result of an alteration of transcription factors required for ICAMl/VCAM-1 gene expression (i.e., NF-KB, IRF-1, C/ EBP, AP-2) or the activation of a repressor of adhesion molecule transcription.…”
Section: Fig 4 Effect Of Fsk Dbcamp and Ne On Tnf-a-inducedmentioning
confidence: 97%
“…Increased intracellular levels of cAMP often results in immunosuppression in a variety of cell types (for review, see Kammer, 1988). For example, increased cAMP levels can suppress the immune response by affecting T-cell transcription of the IL-2 and IFN-y genes (Rappaport and Dodge, i982;Betz and Fox, 1991;Chen and Rothenberg, i994;Neumann et al, 1995). Enhancing cAMP levels in human umbilical vein endothelial cells (HUVEC) and human monocytes inhibits cytokine induction of endothelial leukocyte adhesion molecule (ELAM), also known as Eselectin, and VCAM-1, but has no effect on ICAM-i expression (Pober et al, i993;Ghersa et al, 1994;Ollivier et al, 1996).…”
mentioning
confidence: 99%